Correlation of the activation of the fourth component of complement (C4) with disease activity in systemic lupus erythematosus. Issue 11 (November 1988) - Senaldi, G; Makinde, V A; Vergani, D; Isenberg, D A
Abstract : Levels of C4d, a fragment of C4 generated during activation of the classical complement pathway, were measured in the plasma of 48 patients with systemic lupus erythematosus, 11 with inactive (group 1), 23 with mildly active (group 2), 14 with moderately/severely active disease (group 3), and 30 healthy subjects. Levels of C3d, C4, and C3 were also measured and the C4d/C4 and C3d/C3 ratios calculated. C4d levels correlated with the degree of disease activity, being higher in group 3 than in group 2, in group 2 than in group 1, and in group 1 than in controls. C4d/C4 gave a similar result. Activation indices of the common complement pathway, C3d and C3d/C3, also correlated with disease activity, but in a non-linear relationship, failing to discriminate between patient groups. C4 and C3 showed no correlation with disease activity. These results indicate that indices of C4 activation, C4d and C4d/C4, provide a laboratory measure of disease activity in lupus patients, for whom an objective assessment of the severity of the disease is not readily available.